1989
DOI: 10.1097/00000658-198903000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Selective ERCP and Preoperative Stone Removal in Bile Duct Surgery

Abstract: This project was undertaken to evaluate in a prospective fashion the effects of selective preoperative endoscopic-retrograde cholangiography and stone extraction (ERCP-ST EXTR) on the results of biliary tract surgery. Over a 6-year period, 728 patients with primary or secondary biliary tract disease were admitted to the First Surgical Department, landeskrankenanstalten, Salzburg, Austria. If, based on preoperative screening, the possibility of common bile duct stones (CBDS) existed, the patients were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…Common duct exploration with or without cholecystectomy, however, had been associated with such high figures of 22% complication rate and 4% mortality rate [117]. ERCP and CBDS extraction reduced these complications to 2% and 1%, respectively [117].…”
Section: Simple Choledocholithiasismentioning
confidence: 99%
See 1 more Smart Citation
“…Common duct exploration with or without cholecystectomy, however, had been associated with such high figures of 22% complication rate and 4% mortality rate [117]. ERCP and CBDS extraction reduced these complications to 2% and 1%, respectively [117].…”
Section: Simple Choledocholithiasismentioning
confidence: 99%
“…Common duct exploration with or without cholecystectomy, however, had been associated with such high figures of 22% complication rate and 4% mortality rate [117]. ERCP and CBDS extraction reduced these complications to 2% and 1%, respectively [117]. However, others found no advantage of the combined ERCP and the conventional cholecystectomy over cholecystectomy and common duct exploration [118,119].…”
Section: Simple Choledocholithiasismentioning
confidence: 99%
“…By this means and including ESWL as well as local shocke-wave lithotripsy [52][53][54] the endoscopist is able to treat 90-95% of common bile duct stones with out the need of surgery [55][56][57][58]. Furthermore, it has been shown that selective preoperative endoscopic retrograde cholangiopancreatography and stone removal have very low morbidity and mortality in the laparoscopic treat ment of complicated gallstone disease [59].…”
Section: Common Bile Duct Stone Managementmentioning
confidence: 99%
“…The most significant changes are: (1) the use of pre-and intra-opera tive sonography; (2) the increasing use of video-cholan giography. replacing conventional film cholangiography: (3) the use of fiber-optic choledochoscopy in appropriate cases; (4) the development of endoscopic retrograde chol angiopancreatography (ERCP) and endoscopic papillot omy, and (5) percutaneous removal of stones through the T-drain tract under X-rav control (Burhenne technique) [9][10][11][12],…”
Section: Introductionmentioning
confidence: 99%